Analysis of technology innovation efficiency and its impact factors based on DEA-fsQCA method: Evidence from listed seed companies in China - Ming Mo; Lidanting Zeng (Heliyon)
Seed industry plays a pivotal role in the advancement of national agricultural growth, with seed companies serving as the primary drivers of seed production. The existence of seed companies with the ability to integrate innovation and adapt to market demand plays a crucial role in a nation's capacity to ensure food security over time. This study utilizes micro-data from listed seed companies in China spanning the years 2019–2023 to conduct a comprehensive analysis of enterprise innovation efficiency. The research aims to identify strategies for enhancing innovation efficiency and ultimately fostering development within these seed companies. The findings indicate that: (1) The general level of innovation efficiency among listed seed companies in China exhibits significant potential for enhancement, with technology research and development stage demonstrating higher efficiency levels compared to stage of achievement transformation; (2) The enhancement of innovation efficiency in listed seed companies does not rely solely on any individual factor, but rather necessitates the combined influence of two or more antecedent variables; (3) Listed seed companies in China can enhance their innovation capability through five key approaches: employee-centric, talent and management-focused, talent and scale diversity-driven, talent and government collaboration, and talent and diversity enhancement strategies. The findings presented in this paper are expected to enhance the innovation efficiency of seed companies and offer both policy recommendations and practical guidance for fostering seed industry.